Reliability and validity of the WISC-R for the age range 6 to 11 years in Greece - Σ. Αλεξόπουλος Δημήτριος; Χαρίτου-Φατούρου Μίκα; Σακκά Δέσποινα; Σκαλτσάς Ανδρέας; Βλάχου Όλγα (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF